2022
DOI: 10.3233/prm-220050
|View full text |Cite
|
Sign up to set email alerts
|

Social media and the practice of pediatric physical medicine and rehabilitation in the COVID-19 pandemic: A new era in patient-care

Abstract: Social media represents a significant source of health information for the public, especially during the COVID-19 pandemic where gatherings are limited. It is important for pediatric physical medicine and rehabilitation physicians to understand how their patients use these platforms in order to educate the public and provide sound medical advice on social media. Given the lack of current guidelines on medical education through social media, the purpose of this paper is to provide an overview of various online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…15 This may reflect increasing demand and Internet usage over time. [6][7][8][9] This study found that the majority of centers (79.7%) were updated in the year of 2022. The remaining websites were updated recently, with the latest date listed as 2019.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…15 This may reflect increasing demand and Internet usage over time. [6][7][8][9] This study found that the majority of centers (79.7%) were updated in the year of 2022. The remaining websites were updated recently, with the latest date listed as 2019.…”
Section: Discussionmentioning
confidence: 79%
“…Social media has grown to be a significant outlet for patient education, particularly since the start of the COVID-19 pandemic. 36 Social media is used by nearly 90% of adolescents 8 and its use among United States adults has tripled from 20% to 70% between 2008-2016. 37 This platform of learning can enhance the patient-provider relationship.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When deciding on a program, applicants often consider several key factors, such as curriculum, rotations, compensation, benefits, and research opportunities, typically available on a program's website [1][2][3]. The importance of website information was further emphasized during the pandemic, as many applicants relied upon online resources to guide their decision while face-to-face consultation was limited [4]. As more applicants begin to rely upon program websites for information, the concern becomes whether such websites contain the appropriate amount and types of information for applicants to make an informed decision.…”
Section: Introductionmentioning
confidence: 99%